Oriented mentalization-based treatment for borderline personality disorder patients: preliminary results at Camposampiero Mental Health Center - Stefano Carrera; Guia Pandolfi; Jee Yun Cappelletti; Walter Padoani; Silvia Salcuni (Research in Psychotherapy, 2018)
This contribution presents two brief reports about preliminary results of 18 months of oriented Mentalization-Based Treatment (MBT), with Borderline Personality Disorder patients, recruited at the Camposampiero Mental Health Center. Following in large part Bateman and Fonagy guidelines for MBT in institutional settings, this paper presents preliminary results in two brief reports related to two cohorts of patient underwent to the oriented MBT in Camposampiero Mental Health Center (MHC). In the first study, we analyzed a group of 9 patients: an anamnestic schedule was administered; then, symptoms (SCL-90-R), psychodiagnostic scale and global health functioning (Health of the Nation Outcome Scale, Structured Clinical Interview for DSM-IV Axis II Disorder [SCID-II], Global Assessment of Functioning, [GAF]), data on service impact and service costs (Cassel Community Adjustment Questionnaire, Patient Evaluation Schedule and folder data) were provided at the beginning (T0), at the end of the treatment (T2) and 1 year after the end of the MBT project. The second study showed a micro-analytical change on a second patient cohort (n=6) at T0, 3, 6 and 9 months (T1) were presented considering specifically mentalization (Comparative Psychotherapy Process Scale, Modes of Mentalization Scale, Mentalization Imbalances Scale) and patienttherapist session evaluation trends (Session Evaluation Questionnaire) and patient reflective functioning at T0 and T2 (Reflective Functioning Questionnaire). Aims and hypotheses of the two studies pointed out how the oriented MBT bring to an improvement of the overall functioning of the patients, a reduction of the symptoms, a decrease of the diagnostic criteria for the Borderline Personality Disorder (BPD) and the other Axis II disorders, a reduction of the workload hours for the MHC staff and of the costs of the assistance. The analyses of both the studies were carried out using non-parametric statistics (Friedman test, Spearman correlation, Chi-square). Preliminary results confirmed the improvement in the overall functioning of patients (GAF), the reduction in BPD-related symptoms and in diagnostic criteria for BPD (SCID-II), the improvement of patients’ mentalization skills, and a significant reduction in workload for health staff. Standing the limits and the preliminary results, the two brief reports demonstrate the feasibility of an oriented MBT within an Italian Public Service and the effectiveness of this treatment pathway for patients with BPD, leaving some open questions to stimulate a fruitful clinical discussion.